2017
DOI: 10.1063/1.5001342
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of permeability on the flow past permeable disks at low Reynolds numbers

Abstract: The viscous flow over a thick permeable circular disk in the Reynolds number (Re) range of 10 to 130 and in the Darcy number (Da) range of 10−9 to 1 is examined. Direct numerical simulations are performed on a 2D grid with axisymmetric boundary conditions. Three flow regimes are observed: I, II, and III. In regime I (effectively impervious; Da<10−6), the wake is characterized by the presence of a toroidal vortex whose length is approximately equal to that of an impervious disk. In regime II (transition;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
9
26
0
Order By: Relevance
“…Increasing the Darcy number, the C D slightly decreases first and a significant reduction is successively visible for Da > 1 × 10 −3 . In this range of Da, the drag coefficient follows the scaling C D ∼ Re −1 Da −1 , as reported in[3].…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Increasing the Darcy number, the C D slightly decreases first and a significant reduction is successively visible for Da > 1 × 10 −3 . In this range of Da, the drag coefficient follows the scaling C D ∼ Re −1 Da −1 , as reported in[3].…”
supporting
confidence: 65%
“…Increasing the porosity, and so the permeability, the vortex street formation moves further downstream. More recently, the problem of the flow around porous square cylinders [8,9] and porous disks [3] has been approached numerically. In the latter case, by increasing the disk permeability three different flow regimes have been recognized: (i) first an effectively impervious regime, which is characterized by the presence of a toroidal vortex recirculation region located close to the disk, is observed at low permeability; (ii) Subsequently a transition regime in which the recirculation region shortens and moves downstream occurs for intermediate permeability;…”
Section: Introductionmentioning
confidence: 99%
“…We adopted the modelling approach of ref. 25, where we considered the steady, axisymmetric flow past the permeable disk. In the fluid domain, the steady-state Navier-Stokes equations are solved and inside the permeable disk, the steady-state Darcy-Brinkmann equations are solved.…”
Section: M7 Flow Field Characterization Of the Svrmentioning
confidence: 99%
“…However, our numerical modelling and experimental measurements revealed that the flow through the seed entails strong interactions between neighboring filaments 19,20 , causing the pappus to behave as a permeable membrane. It has been suggested that changing the permeability of a body could be useful to control or suppress the vortex shedding 25 . A recent study has confirmed that the motion of freely falling disks (with > 10 3 ) can be stabilized by a hole in the center of the disk 26 .…”
mentioning
confidence: 99%
“…The velocity deficit behind porous disks is associated with negative pressure (12). A larger vortex with a greater velocity deficit may therefore increase the magnitude of the negative pressure, enhancing drag on the pappus.…”
Section: Resultsmentioning
confidence: 99%